Comparative Effectiveness of Yoga and Exercise on Subjective Well-Being and Emotional Regulation for Elderly in China: A Randomized Controlled Trial - Yuan, Yue; Kang, Manying; Shen, Hongkun (Global Journal of Social Sciences Studies, 2020)
This research aimed to compare the mental effects of yoga and exercise on retired elders: a 3-arm randomized controlled trial (baseline, 12-week-interventions, and 24-week- intervention) on subjective well-being and emotional regulation of Chinese retired elders. Outcomes were Subjective Well-Being Scale (SWBS) to measure subjective well-being, and Emotional Regulation Self-Efficacy Scale (ERSES) to measure emotional regulation. The findings evaluated at baseline, baseline, 12-week, and 24-week. As the result, compared with exercise, yoga exercise can improve more emotional regulation and the subjective well-being of Chinese retired elders. Yoga can accelerate the transformation of specific physical meaning into more profound mental experience, such as the subjective well-being and emotional regulation in Chinese retired elders. This study provides empirical evidence that yoga is an effective practice for the retired elderly to enhance their subjective well-being and emotional regulation. Such method can recommend for the elderly in China where the population of the elderly is growing currently.